2008
DOI: 10.1017/s003329170700267x
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and Stroop interference from age 9 to age 41 years: a meta-analysis of developmental effects

Abstract: The results from this analysis indicate that the Stroop interference effect is not larger in ADHD individuals than in age-matched controls. Further, we did not find evidence for differential maturation rates for persons with ADHD and the control groups. The Stroop interference effect appears to be immune to age, regardless of ADHD status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 56 publications
(46 reference statements)
8
47
0
2
Order By: Relevance
“…Interference control suppressing the dominant response of reading what you see (say 2 when you see 1) is essential for good performance on this task. Two recent meta-analyses revealed that Stroop interference deficits cannot be found consistently in ADHD [30,34]. The absence of a group effect on Opposite Worlds is in keeping with these studies.…”
Section: Discussionmentioning
confidence: 56%
“…Interference control suppressing the dominant response of reading what you see (say 2 when you see 1) is essential for good performance on this task. Two recent meta-analyses revealed that Stroop interference deficits cannot be found consistently in ADHD [30,34]. The absence of a group effect on Opposite Worlds is in keeping with these studies.…”
Section: Discussionmentioning
confidence: 56%
“…Poor interference control has been argued to be one of the core deficits of ADHD (Barkley, 1997) and many studies have indeed found support for an interference control deficit, although findings across studies are not fully consistent (for meta-analyses, see Lansbergen, Kenemans, & van Engeland, 2007;Mullane, Corkum, Klein, & McLaughlin, 2009;Schwartz & Verhaeghen, 2008;van Mourik, Oosterlaan, & Sergeant, 2005). The mixed findings may be explained by several factors, such as the task used, the calculation of the interference effect, and the heterogeneity of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…(Homack & Riccio, 2004). Furthermore, despite these mixed findings, the Stroop task still remains the most frequently used task to examine response inhibition (Schwartz & Verhaeghen, 2008). Therefore, a computerized Stroop task was used to measure effortful control in the present study.…”
Section: Respectively) Effortful Controlmentioning
confidence: 94%
“…While the Stroop task is the most frequently used cognitive task of interference control and response inhibition in ADHD populations (Homack & Riccio, 2004;Schwartz & Verhaeghen, 2008), results have been mixed as to whether the Stroop task distinguishes between ADHD and non-ADHD participants (e.g., Boonstra et al, 2005;Scheres et al, 2004;Homack & Riccio, 2004;Schwartz & Verhaeghen, 2008). For example, in a meta-analysis of 25 studies of Stroop performance comparing individuals with and without ADHD, it was concluded that the Stroop interference effect was not greater for ADHD participants in comparison to non-ADHD participants (Schwartz & Verhaeghen, 2008). The authors suggest that perhaps the Stroop task does not adequately assess response inhibition and inference control in individuals with ADHD, and therefore, other cognitive tasks of response inhibition may be more sensitive to these effects (Schwartz & Verhaeghen, 2008).…”
Section: Primary Aim 1: To Compare Youth With and Without Adhd On Depmentioning
confidence: 99%
See 1 more Smart Citation